1999
DOI: 10.1007/s003300050909
|View full text |Cite
|
Sign up to set email alerts
|

Late aneurysm formation in a femoro-popliteal polytetrafluoroethylene graft

Abstract: Since improvement in the material, true aneurysms and pseudoaneurysm formations have become relatively rare complications after femoro-popliteal reconstruction with polytetrafluoroethylene (PTFE) grafts. We report a case of late graft rupture and pseudoaneurysm formation within the straight femoral part of a femoro-popliteal bypass with reinforced (PTFE-wrapped) Gore-Tex graft. The rupture occurred 7 years after implantation without history of direct traumatization. Intraoperatively the whole bypass showed mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Non-anastomotic disruption of a ringed ePTFE graft has also been described in an above knee femoropopliteal bypass 8 . The rupture occurred within the straight femoral part of the graft seven years after implantation without history of trauma.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Non-anastomotic disruption of a ringed ePTFE graft has also been described in an above knee femoropopliteal bypass 8 . The rupture occurred within the straight femoral part of the graft seven years after implantation without history of trauma.…”
Section: Discussionmentioning
confidence: 85%
“…An association with mechanical stress might also be discussed in this case as two thrombo-embolectomy manoeuvres were performed four years after implantation. It seems unlikely that damage to the wall during these manoeuvres would lead to graft disruption three years later, but mechanical stress to the graft during the period of thrombosis distal to the knee joint might have accelerated the degeneration of the wall by superimposed reflected pulsewaves 8 …”
Section: Discussionmentioning
confidence: 99%
“…1 On the other hand, there were no graft aneurysms observed in a study with a 7year followup of 90 patients who underwent femoropopliteal graft implantation using ePTFE grafts. 17 The first case of reinforced ePTFE graft aneurysm was reported by Campbell et al 18 in a femoro popliteal bypass graft in 1976, followed by other cases by Biederer et al 12 and Punnam et al 19 Aneurysm of ePTFE axillofemoral graft was reported by Oz et al 20…”
Section: Discussionmentioning
confidence: 97%
“…When considering the treatment options for such a pseudoaneurysm, open surgical excision of the damaged portion and repair by interposition graft remains the gold standard procedure. 12,18 However, percutaneous endovas cular exclusion of the aneurysm has been used in such cases with increasing frequency, as the procedure is easy to carry out and it is less risky, than open surgical repair performed under general anesthesia. Moreover, it is cost effective and is carried out as a day case procedure.…”
Section: In 2002mentioning
confidence: 99%
“…Pseudoaneurysm formation has been reported in the body of a PTFE graft rather than at the anastomotic site. 3 Although aneurysm development after prosthetic bypass is well known in the groin, it is absent in literature dealing with prosthetic bypass distal to the popliteal artery. 4…”
Section: Introductionmentioning
confidence: 99%